2008
DOI: 10.1111/j.1749-8198.2008.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Modeling as a Tool for Understanding the Landscape Ecology of Southern Pine Beetle Infestations in Southern Appalachian Forests

Abstract: The forests of southeastern North America are influenced by a variety of disturbances including fire and insect outbreaks. In this paper, we discuss the role of disturbances in structuring forest landscapes with particular emphasis placed on the reciprocal interaction between forest structure and outbreaks of the southern pine beetle (Dendroctonus frontalis Zimmermann). We highlight work in which we are currently involved to illustrate the importance and utility of using spatially explicit forest modeling as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Linking field studies with predictive models can provide information on spatial spread patterns, rates of spread and the impact of external factors influencing spread (Petrovskii and Bai-Lian 2006). In recent times, researchers have increasingly used spatial modeling procedures as a means to target invasive species and develop better management strategies (Cairns et al 2008;Eppstein and Molofsky 2007;Higgins and Richardson 1996;Wadsworth et al 2000). But many existing models are statistically based and do not explicitly address the spatio-temporal components and complexity of invasive species propagation (Collingham et al 2000;Goslee et al 2001).…”
Section: Unionmentioning
confidence: 99%
“…Linking field studies with predictive models can provide information on spatial spread patterns, rates of spread and the impact of external factors influencing spread (Petrovskii and Bai-Lian 2006). In recent times, researchers have increasingly used spatial modeling procedures as a means to target invasive species and develop better management strategies (Cairns et al 2008;Eppstein and Molofsky 2007;Higgins and Richardson 1996;Wadsworth et al 2000). But many existing models are statistically based and do not explicitly address the spatio-temporal components and complexity of invasive species propagation (Collingham et al 2000;Goslee et al 2001).…”
Section: Unionmentioning
confidence: 99%
“…Also, simulated southern pine beetle outbreaks over time tend to decrease the aggregation of host species on the landscape by fragmenting large patches into smaller ones, thereby reducing the severity of future outbreaks. The results of this study indicate that when considering alternative restoration strategies for insect-affected landscapes, it is necessary to consider the patterns of hosts on the landscape as well as the landscape composition (Cairns et al 2008a(Cairns et al , 2008b.…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…Most recently, we used a modeling approach to show how landscape structure and herbivory interact to influence outbreaks of SPB in a landscape representative of the southern Appalachian Mountains (Cairns et al 2008a(Cairns et al , 2008a. We found that landscape composition was less important than host aggregation in determining the severity of SPB outbreaks.…”
Section: Spatial Characteristicsmentioning
confidence: 99%
“…6). More complex simulation models may additional include the life cycle of the host crop, the feast of the pest agents to distance crops as well as the influence of several other biotic and abiotic factors (Andrade-Piedra et al 2005;Kaundal et al 2006;Cairns et al 2008;Khaliq et al 2014). Thus, pest forecasting is a fundamental step in creating proper IPM programs (Van Maanen and Xu 2003).…”
Section: Introductionmentioning
confidence: 99%